Penerapan Terapi Rendam Kaki Di Air Hangat Dengan Campuran Garam dan Serai Untuk Menurunkan Tekanan Darah Dengan Hipertensi - Sri Sundari; Mona Hastuti (STIKES Columbia Asia Medan, 2025)
Hypertension is a condition where there is an increase in blood pressure in the arteries. A person can be said to be hypertensive if the person has systolic blood pressure >140 mmHg and diastolic >80 mmHg. One way to lower blood pressure in hypertensive patients is by soaking the feet in warm water with a mixture of salt and lemongrass. This article uses a case study design and the subjects used in this case are hypertensive patients in the Mabar Hilir environment. The results of implementing the intervention found that there was an effect of warm water foot soak therapy with a mixture of salt and lemongrass with blood pressure observations of 135/80 mmHg. Conclusion: Application of warm water foot soak therapy with a mixture of salt and lemongrass can reduce blood pressure in hypertension patients. The advice is that patients can change their lifestyle to a healthier lifestyle, reduce risk factors for hypertension and continue to carry out regular health checks.